The Effect Of Current Ratio (Cr) And Debt To Asset Ratio (Dar) On Net Profit Margin (Npm) - Siti Sonia; Nufzatutsaniah Nufzatutsaniah (Indonesian Development of Economics and Administration Journal, 2024)
This research aims to find out whether the Current Ratio (CR) and Debt to Asset Ratio (DAR) have an effect on the Net Profit Margin (NPM) at PT Gajah Tunggal Tbk for the 2013–2022 period. This research uses a descriptive method with a quantitative approach. The population used in this research is the financial report of PT Gajah Tunggal Tbk, while the sample used is the profit and loss report and balance sheet of PT Gajah Tunggal Tbk for the 2013–2022 period. The data analysis method uses descriptive statistical analysis tests, classical assumption tests, multiple linear regression tests, coefficient of determination tests, and hypothesis tests with the help of the SPSS version 27 program. The results of this research show that the Current Ratio (CR) has a partial and significant effect on Net Profit Margin (NPM). Debt to Asset Ratio (DAR) has no partial and significant effect on Net Profit Margin (NPM). Current Ratio (CR) and Debt to Asset Ratio (DAR) do not have a significant effect on Net Profit Margin (NPM). The coefficient of determination is 0.425 or 42.5%. This means that the variables Current Ratio (CR) and Debt to Asset Ratio (DAR) have an influential contribution of 42.5% to Net Profit Margin (NPM), while the remainder (100% - 42.5% = 57.5%) is influenced by factors others not researched.